Changes of Insulin Resistance and Adipokines Following Supplementation with Glycyrrhiza Glabra L. Extract in Combination with a Low-Calorie Diet in Overweight and Obese Subjects: a Randomized Double Blind Clinical Trial - Mohammad Alizadeh; Nazli Namazi; Elham Mirtaheri; Nafiseh Sargheini; Sorayya Kheirouri (Tabriz University of Medical Sciences, 2018)
Purpose: Adipose tissue is a highly active endocrine organ which plays a key role in energy homeostasis. The aim of this study was to determine the effects of dried licorice extract along with a calorie restricted diet on body composition, insulin resistance and adipokines in overweight and obese subjects. Methods: Sixty-four overweight and obese volunteers (27 men, 37 women) were recruited into this double-blind, placebo-controlled, randomized, clinical trial. Participants were randomly allocated to the Licorice (n=32) or the placebo group (n=32), and each group received a low-calorie diet with either 1.5 g/day of Licorice extract or placebo for 8 weeks. Biochemical parameters, anthropometric indices, body composition and dietary intake were measured at baseline and at the end of the study. Results: A total of 58 subjects completed the trial. No side effects were observed following licorice supplementation. At the end of the study, waist circumference, fat mass, serum levels of vaspin, zinc-α2 glycoprotein, insulin and HOMA-IR were significantly decreased in the intervention group, but only the reduction in serum vaspin levels in the licorice group was significant when compared to the placebo group (p<0.01). Conclusion: Supplementation with dried licorice extract plus a low-calorie diet can increase vaspin levels in obese subjects. However, the anti-obesity effects of the intervention were not stronger than a low-calorie diet alone in the management of obesity.